Peran Kepala Madrasah sebagai Manajer dalam Peningkatan Ektrakurikuler Keagamaan di MTs Ar-Rahman Nglaban Jombang - Desy Naelasari; Sulastri Bin Abbas (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
The head of the madrasa is not only a manager or leader, but the head of the madrasa also provides support to students so that they can take part in religious extracurricular activities in an orderly manner. As the head of the madrasa at MTs Ar-Rahman Nglaban Jombang who does not only carry out his duties and obligations as the head of the madrasa. However, increasing religious extracurricular activities (BTQ). The role of the madrasa principal as a manager in improving religious extracurricular activities at MTs Ar-Rahman Nglaban Jombang, focuses on religious extracurricular activities (BTQ), as well as the method used in BTQ religious extracurricular activities, namely the Iqra' method. Supporting factors for madrasah principals in increasing religious extracurricular activities are support from the school, parents, and the provision of adequate infrastructure. The inhibiting factor for the madrasah principal in increasing religious extracurricular activities is the lack of parental support, teachers who lack cooperation in religious extracurricular activities, and the students themselves